2010
DOI: 10.1210/jc.2009-2773
|View full text |Cite
|
Sign up to set email alerts
|

Lipoatrophy Induced by Subcutaneous Insulin Infusion: Ultrastructural Analysis and Gene Expression Profiling

Abstract: Our results clearly indicate that the remarkable reduction in fat cell lipid droplets and adipocyte size justifies the decrease of SAT without a reduction in adipocyte number because of necrosis or apoptosis. Thus, immune cells and any other toxic damaging fat cells were not involved in the generation of LA. We speculate that adipocytes chronically exposed to high local insulin concentrations could become severely insulin resistant, dramatically increasing lipolysis and giving rise to "slimmed cells." Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Adipocytes were shrunk and reduced in number, consistent with previous reports [3-5]. Milan et al [6] provided ultrastructural analyses on chronic lipoatrophies, having existed for eight months to six years (median 26 months) in three patients using Humalog™. They showed fat cell atrophy, deposition of amyloid, and numerous perivascular preadipocytes.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Adipocytes were shrunk and reduced in number, consistent with previous reports [3-5]. Milan et al [6] provided ultrastructural analyses on chronic lipoatrophies, having existed for eight months to six years (median 26 months) in three patients using Humalog™. They showed fat cell atrophy, deposition of amyloid, and numerous perivascular preadipocytes.…”
Section: Introductionsupporting
confidence: 85%
“…Various subcutaneously administered pharmaceuticals including hormone preparations [1-6,8-13,20,21] and vaccines [22] may be the cause of LIL. In cases of incipient insulin-induced LIL, the idiosyncratic trigger can obviously be turned off by systemic corticosteroid application, despite ongoing subcutaneous insulin administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is suggestive of a hypersensitivity reaction, which has led to attempts to treat LA with the mast cell stabiliser sodium cromoglicate [25]. However, in their study of histological samples from 3 affected patients with T1D, Milan et al [3] argued against an inflammatory process in the development of LA. They proposed that LA results from adipocyte delipidation secondary to local insulin resistance, but their analysis may have been limited by only sourcing samples from areas of established LA and not, for example, from the edges between normal and LA tissue [6].…”
Section: Discussionmentioning
confidence: 99%
“…An underlying immunological mechanism was originally proposed by Paley [1] in 1953. Peters and Winkelmann [2] suggested that transitory lymphocyte-mediated panniculitis is the primary lesion that progresses to LA, which has recently been called into question [3]. …”
Section: Introductionmentioning
confidence: 99%